Layperson Perception of Reflux‐Related Symptoms - Jakob L. Fischer; Anthony M. Tolisano; Alvaro I. Navarro; Lily Trinh; Waleed M. Abuzeid; Ian M. Humphreys; Nadeem A. Akbar; Sharan Shah; John S. Schneider; Charles A. Riley; Edward D. McCoul (OTO Open, 2023)
Abstract Objective To assess for differences of intended meaning in the description of reflux‐related symptoms among otolaryngology patients and clinicians. Study Design Cross‐sectional survey‐based study. Setting Five tertiary, academic otolaryngology practices. Methods Between June 2020 and July 2022, a questionnaire consisting of 20 common descriptors of reflux‐related symptoms within four domains (throat‐, chest‐, stomach‐, and sensory‐related symptoms) was completed by patients. Attending otolaryngologists at five academic medical centers then completed the same survey. The primary outcome was to assess differences in patient and clinician perceptions of reflux‐related symptoms. Differences based on geographic location was a secondary outcome. Results A total of 324 patients and 27 otolaryngologists participated. Patients selected a median of six terms compared with 10.5 for otolaryngologists (p < .001). Otolaryngologists were more likely to select sensory symptoms (difference: 35.8%; 95% confidence interval [CI]: 19.2%, 52.4%), throat‐related symptoms (32.4%; 21.2, 43.6%), and chest‐related symptoms (12.4%; 8.8, 15.9). Otolaryngologists and patients were equally likely to consider stomach symptoms as related to reflux (4.0%, −3.7%, 11.7%). No significant differences were identified based on geographic location. Conclusion There are differences between otolaryngologists and their patients in the interpretation of the symptoms of reflux. Patients tended to have a narrower interpretation of reflux with symptoms primarily limited to classic stomach‐related symptoms, while clinicians tended to have a broader definition of reflux that included extra‐esophageal manifestations of disease. This has important counseling implications for the clinician, as patients presenting with reflux symptoms may not comprehend the relationship of those symptoms to reflux disease.